Pengaruh Penggunaan E-Modul Berbasis Strategi Meta Kreatif terhadap Kreativitas Mahasiswa dalam Pembelajaran Penelitian Tata Rias dan Kecantikan - Miftakhurrohmah Miftakhurrohmah; Rahmiati Rahmiati (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Creativity is the ability to generate new and innovative ideas that are valuable and useful in a particular context. In higher education, creativity is very important because it encourages students to think critically, solve problems effectively, and innovate in their fields of study. This study aims to test the effectiveness of using e-modules based on metacreative strategies in improving students' creativity in the Makeup and Beauty Research course at Padang State University. This type of research uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The population of this study was students of the Makeup and Beauty study program class of 2021 with a sample size of 53 people. Data analysis techniques in this research consist of descriptive statistics, creativity assessment scale, n-gain score test, prerequisite analysis test, and hypothesis testing (Independent sample t-test). The results showed that there was a significant increase in the level of student creativity in the experimental group and the control group. The average pretest score in the control group was 56.72 and the posttest was 64.07 with an N-gain of 0.17 (low category). Meanwhile, the experimental group had an average pretest score of 60.00 and a posttest of 78.77 with an N-gain of 0.46 (moderate category). The results of the hypothesis test using the independent sample t-test showed a sig.(2-tailed) value of 0.000 <0.05, so there was a significant difference between the experimental group using e-modules based on meta-creative strategies and the control group using conventional learning methods. This shows that the use of e-modules based on meta-creative strategies is effective in improving student creativity.